In the Public Eye : A History of Reading in Modern France, 1800-1940 - Allen, James Smith (Book collections on Project MUSE., 2014)
Robert Darnton, Roger Chartier, and others have written much on the history of reading in the Old Regime, but this is the first broad study of reading to focus on the period after 1800. How and why did people understand texts as they did in modern France? In answering this question, James Allen moves easily from one interpretive framework to another and draws on a wide range of sources--novels, diaries, censor reports, critical reviews, artistic images, accounts of public and private readings, and the letters that readers sent to authors about their books. As he analyzes reading ""in the pu